A Budget Structured to Reflect Economic Objectives: Discussion - Hellmuth, William F.; Ott, David J. (Journal of Finance, 1973)
William F. Hellmuth, David J. Ott, A Budget Structured to Reflect Economic Objectives: Discussion, The Journal of Finance, Vol. 28, No. 2, Papers and Proceedings of the Thirty-First Annual Meeting of the American Finance Association Toronto, Canada, December 28-30, 1972 (May, 1973), pp. 496-500